2006
DOI: 10.1001/jama.295.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Low-Fat Dietary Pattern and Risk of Invasive Breast Cancer

Abstract: ClinicalTrials.gov Identifier: NCT00000611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
170
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 693 publications
(181 citation statements)
references
References 50 publications
7
170
0
4
Order By: Relevance
“…Total fat intake was 31.15 E% for the first tertile and 39.2 E% for the highest tertile, after adjustment for confounders). Similar conclusions were reached in other studies (Prentice et al, 2006;Chlebowski et al, 2006;Borugian et al, 2004;McEligot et al, 2006). Total fat intake has also been associated with higher risk of lung cancer.…”
Section: Cancersupporting
confidence: 91%
“…Total fat intake was 31.15 E% for the first tertile and 39.2 E% for the highest tertile, after adjustment for confounders). Similar conclusions were reached in other studies (Prentice et al, 2006;Chlebowski et al, 2006;Borugian et al, 2004;McEligot et al, 2006). Total fat intake has also been associated with higher risk of lung cancer.…”
Section: Cancersupporting
confidence: 91%
“…While recent epidemiological evidence supports a role for dietary fibre intake in relation to lower endogenous hormone levels (Rock et al, 2004;Prentice et al, 2006), the question remains unsettled. In our study of endogenous oestrogen levels in postmenopausal women, oestradiol decreased monotonically from 10.6 to 6.2 pg ml À1 from the lowest to the highest quintile of dietary fibre intake (median intake of 9.9 -21.7 g per 1000 kcal), whereas soluble fibre, after adjustment for dietary fibre, was associated with an increase in oestradiol from 6.8 to 11.5 pg ml À1 from the lowest to the highest quintile of intake (median intake of 2.9 -7.1 g per 1000 kcal) (Monroe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The initial design of the study was based on disease stage but not on tumor characteristics. There may be differential responses to a dietary intervention based on hormone receptor status (10). Indeed, the recent results from the Women's Health Initiative Dietary Modification Trial reported differential effects of the low-fat eating pattern by tumor hormone receptor status: the hazard ratio for progesterone receptor -negative breast cancers was 0.76 (95% confidence interval, 0.63-0.92; P < 0.004; ref.…”
mentioning
confidence: 99%
“…Indeed, the recent results from the Women's Health Initiative Dietary Modification Trial reported differential effects of the low-fat eating pattern by tumor hormone receptor status: the hazard ratio for progesterone receptor -negative breast cancers was 0.76 (95% confidence interval, 0.63-0.92; P < 0.004; ref. 10). Although the Women's Health Initiative tested breast cancer incidence and not recurrence, preliminary results from another dietary intervention trial in breast cancer survivors also reported differential effects of the intervention by hormone receptor status (11).…”
mentioning
confidence: 99%